Clusters of GaAs prepared by quantum mechanical DFT and the nanowire raman spectra - Ahmad Nazrul Rosli,; Hasan Abu Kassim,; Keshav N. Shrivastava, (Universiti Kebangsaan Malaysia, 2013)
We studied the clusters of GaAs by using the density functional theory simulation to optimize the structure. We determined the binding energy, bond lengths, Fermi energy and vibrational frequencies for all of the clusters. We use the Raman data of nanowires of GaAs to compare our calculated values with the experimental values of the vibrational frequencies. The nanowire of GaAs gives a Raman line at 256 cm-1 whereas in the bipyramidal Ga2As3 the calculated value is 256.33 cm-1. Similarly 285 cm-1 found in the experimental Raman data agrees with 286.21 cm-1 found in the values calculated for Ga2As2 (linear) showing that linear bonds occur in the nanowire. The GaAs is found in two structures zinc-blend as well as wurtzite structures. In the nanowire mixed structures as well as clusters are formed.